Revisiting 'community' in community-based natural resource management - Kumar, C. (2005)
This article concerned with the diverse nature and interest in the concept of 'community' and especially as it applies to community-based natural resource management projects that have grown in emphasis during the past twenty years. Despite all the rhetoric about community and its reference in a ritualistic manner in projects and policy documents, often contrary experiences and mixed results in the field have started stirring negative reactions from various quarters. This article dwelves into the challenges and dilemas, which the focus on 'community', with its lack of specificity, has conjured up for practitioners, policy makers and academicians alike.